(untitled) (International Journal of Environmental Sciences, 2025)
Background: Cervical cancer treatment outcomes were influenced not only by medical procedures but also by sociodemographic, clinical, and personality characteristics. Understanding these factors was essential for optimizing therapy success. Objective: This study aimed to analyze the interplay between knowledge, education, stage of cervical cancer, length of illness, and personality in determining treatment success among cervical cancer patients. Methods: A quantitative, cross-sectional study was conducted in 2024 at General Hospital, Semarang, involving 135 cervical cancer patients. Data were collected using a validated and authorized questionnaire. Independent variables included knowledge, educational, stage of cervical cancer, length of illness, personality while the dependent variable was treatment success. Data were analyzed through univariate, bivariate (Somers’d test), and multivariate analyses using ordinal logistic regression. Results: The respondents had good knowledge (58.5%), elementary education (57.8%), advanced-stage disease (57.8%), treatment success was categorized as good in 58.3% of patients. Knowledge (p < 0.001, r = 0.960), and education (p < 0.001, r = 0.479) were significantly associated with treatment success. Multivariate analysis showed that these five variables explained 83% of the variance in treatment success (Cox and Snell R² = 0.830). Conclusions: Higher knowledge, and better education were associated with greater treatment success in cervical cancer patients. Interventions that targeted patient education, early detection, and psychosocial support were recommended to enhance treatment outcomes.